2002
DOI: 10.1007/s00065-002-1059-3
|View full text |Cite
|
Sign up to set email alerts
|

Technique of Biologic Fixation of Subtrochanteric Femoral Fractures with Dynamic Condylar Screw (DCS)

Abstract: ObjectiveTreatment of closed comminuted subtrochanteric fractures using the dynamic condylar screw (DCS), with the goal of reducing operating time, blood loss, and incidence of delayed union. IndicationsComminuted subtrochanteric fractures, especially types B and C of the AO classification. Fracture line extending to piriformis fossa precluding use of an intramedullary device. Poor general condition, i.e., unable to withstand prolonged anesthesia as required in open reduction and internal fixation (ORIF)/naili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Vaidya and colleagues reported on biologic fixation of closed multifragmentary subtrochanteric fractures with the DCS inserted through small proximal and distal incisions and slid deep to vastus lateralis under radiographic control [41]. Union was achieved in all 31 patients: They concluded that biological fixation was better than open insertion in respect to blood loss, operative time and union rate.…”
Section: Operative Managementmentioning
confidence: 96%
“…Vaidya and colleagues reported on biologic fixation of closed multifragmentary subtrochanteric fractures with the DCS inserted through small proximal and distal incisions and slid deep to vastus lateralis under radiographic control [41]. Union was achieved in all 31 patients: They concluded that biological fixation was better than open insertion in respect to blood loss, operative time and union rate.…”
Section: Operative Managementmentioning
confidence: 96%